Is grand multiparity a risk factor for the development of postmenopausal osteoporosis? - Peker N (Dove Medical Press, 2018)
Nuri Peker,1 Özge Çeliker Tosun2 1Department of Obstetrics and Gynecology, İstinye University Bahçeşehir Liv Hospital, Istanbul, Turkey; 2School of Physiotherapy, Dokuz Eylul University, Izmir, Turkey Objective: In this study, we investigated the relationship between the development of postmenopausal osteoporosis and parity.Materials and methods: The retrospective study included 129 postmenopausal women who were divided into three groups depending on the number of parity: Group I,<5; Group II, 5–9; and Group III, ≥10. The mean age of the subjects was 57.71±5.02 years.Results: No significant difference was found among the three groups regarding body mass index values, duration of menopause, mean thyroid stimulating hormone values and frequency of diabetes. Among the three groups, no significant difference was found in terms of the frequency of lumbar osteoporosis (p>0.05), whereas a significant difference was found regarding the frequency of femoral osteoporosis (p=0.012; p<0.05).Conclusion: It was revealed that femoral bone mineral density significantly decreased as the number of parity increased. Keywords: menopause, osteoporosis, parity